Reconstruction of the TPQ Quality Assurance Paradigm: Integration of the Khoiro Ummah Concept and the PPEPP Cycle in the Digital Era - Khoirul Anwar; Olivia Fachrunnisa; Ridho Okthadiansyah (Civiliza Publishing, Indonesia., 2026)
The digital era brings a double disruption to the Al-Qur'an Education Park (TPQ), namely the demand for technological adaptation as well as the threat of moral decline in Early Childhood and Elementary School (Alpha Generation). On the other hand, conventional TPQ governance is generally still traditional and has not touched the aspect of systematic quality standardization. This article aims to reconstruct the TPQ quality assurance paradigm through a literature study approach (library research). Reconstruction is carried out by integrating the theological-philosophical value of the concept of Khoiro Ummah (QS. Ali Imran: 110) with modern management instruments, namely the PPEPP cycle (Determination, Implementation, Evaluation, Control, and Improvement). The results of the conceptual study formulated four new quality pillars: (1) Qur'an-Based Content Standards Based on Digital Literacy and Manners, (2) TPQ Adaptive PPEPP Cycle, (3) Standardization of Asatidz Techno-Pedagogic Competencies, and (4) External Evaluation Based on Digital Parent Partnerships. This integration results in a holistic quality assurance model, where the quality of TPQ is no longer measured by cognitive reading fluency, but rather the formation of an Islamic personality (syakhsiyah Islamiyah) that is responsive to digital reality.